2013
DOI: 10.1177/0954411912474781
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff repair: A biomechanical ex vivo ovine study

Abstract: The purpose of this study was to assess load to failure of sutures, suturing techniques, and suture anchors used in rotator cuff surgery in order to explore their weaknesses. Ten types of sutures (absorbable and nonabsorbable), four types of suturing techniques, and eight types of suture anchors (bioabsorbable and metallic) were tested. Material Testing Machine and attached load cell were used to test the biomaterials in ex vivo ovine tissues. The results show that the mean load to failure and stiffness were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…As we all know that the critical point of RCT requires the repaired site tend-to-bone surface healing [ 47 , 48 ]. One of the most common reasons for the failure of an RCR is the retear because of nonhealing of the primary repair [ 49 ]. A study by Park et al [ 27 ] showed that approximately 50% of repaired rotator cuffs do not heal completely, though the surgical techniques were used.…”
Section: Discussionmentioning
confidence: 99%
“…As we all know that the critical point of RCT requires the repaired site tend-to-bone surface healing [ 47 , 48 ]. One of the most common reasons for the failure of an RCR is the retear because of nonhealing of the primary repair [ 49 ]. A study by Park et al [ 27 ] showed that approximately 50% of repaired rotator cuffs do not heal completely, though the surgical techniques were used.…”
Section: Discussionmentioning
confidence: 99%
“…Ωστόσο η ανατομία του κονίκλου διαφέρει από την αντίστοιχη του ανθρώπου και οι μελέτες αυτές περιλαμβάνουν κυρίως τον υποπλάτιο, διότι ο συγκεκριμένος περνά κάτω από τόξο αντίστοιχο του κορακοακρωμιακού στον ανθρώπινο οργανισμό (239). Οι ρήξεις του στροφικού πετάλου που συναντούμε στον ανθρώπινο οργανισμό είναι συνήθως μεγάλες και χρόνιες στη φύση τους, καθιστώντας πιθανότατα το πειραματικό μοντέλο του αμνού ιδανικό για μελέτη τεχνικών και υλικών συρραφής και καθήλωσης των τενόντων στο μείζον βραχιόνιο όγκωμα (in vitro) (240). Τέτοιου είδους πειραματόζωα έχουν χρησιμοποιηθεί και για μελέτη των αλλαγών και της εκφύλισης των αντίστοιχων μυϊκών ομάδων (189).…”
Section: βασικη ερευνα και πειραματικα μοντελα στην μελετη εκφυλισης των μυων στροφικου πεταλου-συσχετιση με την παρουσα ∆ι∆ακτορικη ∆ιατunclassified